Application of Data Mining to Group the Spread of Covid-19 in West Java Province, Indonesia Using the K-Means Algorithm - Ronald Sebastian; Christina Juliane (Indonesian Journal of Artificial Intelligence and Data Mining, 2022)
Covid-19 cases in Indonesia have not subsided. The spread of COVID-19 cases has reached provinces in Indonesia such as West Java, which is one of the many locations where the virus has been detected. COVID-19 cases have spread to 28 districts and cities in West Java. Researchers must determine the level of distribution of COVID-19 cases which are divided into three clusters, namely high, medium, and low clusters, so that the West Java Regional Government can take action in an effort to prevent the spread of COVID-19 cases. Researchers use data mining and the K-means Clustering algorithm. to examine the distribution of COVID-19 cases. This data set for the study of the spread of COVID-19 in West Java Province, covers data for the period August 1, 2020 to July 15, 2022. To perform K-means Clustering on the data set, researchers used RapidMiner Studio 9.10. The results of this study indicate that in West Java there are two cities with the highest Covid-19 clusters, namely Bekasi and Depok, six cities and district in the medium cluster, namely city of Bogor, Bandung, and Karawang District, Bekasi, Bandung and Bogor, and The twenty district/cities in the lowest cluster for the spread of COVID-19 cases are the cities of Banjar, Cimahi, as well as the districts of West Bandung, Ciamis, Cianjur, Cirebon, Garut, Indramayu, Kuningan, Majalengka, Pangandaran, Purwakarta, Subang, Sukabumi, Sumedang, Tasikmalaya.